2016
DOI: 10.1111/are.13149
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo selection of probiotic purple nonsulphur bacteria with an ability to inhibit shrimp pathogens: acute hepatopancreatic necrosis disease-causing Vibrio parahaemolyticus and other vibrios

Abstract: Shrimp cultivation has been faced with huge losses in productivity caused by infectious shrimp pathogenic vibrios, especially Vibrio parahaemolyticus that causes acute hepatopancreatic necrosis disease (AHPND). Hence, purple nonsulphur bacteria (PNSB) were isolated from shrimp ponds for investigating their abilities to control shrimp pathogenic Vibrio spp. and their use as probiotics for sustainable shrimp cultivation. Based on their probiotic properties, strains S3W10 and SS15 were selected because of their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
(47 reference statements)
1
20
1
Order By: Relevance
“…A hypothesis might be that PNSB in the feed were able to colonize the gastrointestinal tract and assist the digestion. Chumpol et al (2017) for example observed that shrimp administered with live PNSB are able to colonize the gastrointestinal tract and assist the digestion by excreting proteases, lipases and amylases. Our study was performed with freeze-dried PNSB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hypothesis might be that PNSB in the feed were able to colonize the gastrointestinal tract and assist the digestion. Chumpol et al (2017) for example observed that shrimp administered with live PNSB are able to colonize the gastrointestinal tract and assist the digestion by excreting proteases, lipases and amylases. Our study was performed with freeze-dried PNSB.…”
Section: Resultsmentioning
confidence: 99%
“…sphaeroides have antimicrobial properties (Kaspari & Klemme, 1977). Chumpol et al (2017) have performed a similar screening of PNSB on V. harveyi and V. vulnificus. They isolated 185 PNSB species from shrimp ponds and discovered 10 strains with anti- Vibrio potential belonging to the species Rb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two common invertebrate pathogens, Vibrio and Aeromonas , have developed resistance to antibiotics; consequently, probiotics are quickly becoming a tool in the aquaculture industry to reduce losses caused by the most common infectious diseases. As a result, research into alternative probiotic treatments has increased, and a number of effective probiotics that inhibit aquaculture pathogens have been identified . Bacterial probiotics treatments, including members of the genera Lactobacillus, Carnobacterium, Bacillus , and Pseudomonas , have been shown to provide protection from disease in turbot, salmon, trout, cod, crab, prawns, oysters, and others …”
Section: How Are Probiotics Being Used To Mitigate Infectious Pathogens?mentioning
confidence: 99%
“…As a result, research into alternative probiotic treatments has increased, and a number of effective probiotics that inhibit aquaculture pathogens have been identified. 22 Bacterial probiotics treatments, including members of the genera Lactobacillus, Carnobacterium, Bacillus, and Pseudomonas, have been shown to provide protection from disease in turbot, salmon, trout, cod, crab, prawns, oysters, and others. 19,21,23 Although aquaculture currently has one of the most diverse arrays of probiotic organisms that are being used to mitigate pathogens, claims of beneficial probiotic effectiveness are rarely quantified in controlled studies and, surprisingly, "manufacturers of foods and supplements are not required to obtain premarket approval of claims of efficacy or safety."…”
Section: Probiotics To Reduce Infectious Disease Impacts On Food Prodmentioning
confidence: 99%